Institutional Communication in the Digital Age: Innovative Strategies for Deepening Public Engagement through the Synergy of Knowledge Management and Innovation - Ouldhali, Mohamed (Journal of Humanities & Social Sciences, 2025)
Over the past two decades, the world has undergone an unprecedented digital revolution that has fundamentally reshaped numerous sectors, particularly within business and institutional environments. In this evolving context, corporate communication has transcended its traditional role as a mere conduit for information exchange to become a strategic asset for reinforcing institutional identity, managing reputational capital, and shaping public opinion. Moreover, it has become a foundational pillar for cultivating sustainable relationships with diverse stakeholder groups, both internal and external to the organization. Given the accelerating pace of digitalization, organizations can no longer sustain their competitiveness or long-term viability without critically reassessing and adapting their communication strategies to align with emerging technological paradigms. Within this strategic landscape, knowledge management stands out as a pivotal enabler, empowering organizations to harness, structure, and analyze their intellectual assets effectively. It facilitates informed decision-making and fosters a culture of continuous innovation. Concurrently, cutting-edge digital technologies—such as artificial intelligence, big data analytics, and extended reality—are demonstrating remarkable potential in enhancing communication effectiveness, transparency, and audience engagement. Consequently, digital transformation is no longer an optional enhancement but a strategic imperative that compels institutions to implement innovative solutions aimed at optimizing user experience and consolidating competitive advantage in an increasingly dynamic environment. This study seeks to critically examine the interplay between corporate communication and knowledge management in advancing organizational strategic objectives. Particular attention is given to the transformative impact of digital technologies on institutional interaction strategies. Furthermore, the research investigates the role of emerging tools—especially extended reality—in fostering deeper and more effective audience engagement, thereby strengthening institutional loyalty and promoting sustainable development. Through this lens.
Keywords: Corporate Communication; Knowledge Management; Innovation; Audience Engagement; Digital Transformation